Socioeconomic inequality, health inequity and well-being of transgender people during the COVID-19 pandemic in Nigeria. - Folayan, Morenike Oluwatoyin; Yakusik, Anna; Enemo, Amaka; Sunday, Aaron; Muhammad, Amira; Nyako, Hasiya Yunusa; Abdullah, Rilwan Mohammed; Okiwu, Henry; Lamontagne, Erik (BMC Public Health, 2024)
We aimed to explore socioeconomic inequality, health inequity, and the well-being of transgender people during the COVID-19 crisis in Nigeria.